(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2011)
Without attempting an exhaustive reading of the extensive literature that has been around a school of thought that has marked an important research agenda in the field of public administration in Mexico. This work is limited to return to some reflections of the author from certain works, mostly published in Mexico on the socalled neo-institutionalist thinking. The main result of the literature review presented in this work, although it certainly is a selective review offers, at least we hope, to reflect certain key theoretical and size help to spread both the scope and limits of current neo-institutionalist thinking, particularly in light of recent studies that have been made about government and public administration in Mexico.